Protecting 3D service marks in the EU: the trademark registration dilemma - Sīlis, Georgs (Riga Graduate School of Law, 2020)
The thesis aims to illuminate the ill-defined requirements and their theoretical applicability of registering a three-dimensional service mark consisting of a store layout in the wake of the Apple judgement in 2014, granting for the possibility of registering a sign lacking in absolute sizes, relative proportions, as long as the sign passes the “departs significantly” criterion, a relative concept primed for misapplication. Given the market power of certain multinational companies, granting trademark protection on their business environs in the EU may result in distorted competition by abusing the existing legal system. Throughout the analysis the thesis concludes that minimalism-inspired layout marks ought to be regarded as a priori failing the absolute grounds for refusal to register due to their inherent inability to function as source-identifiers if they are not combined with figural or semantic signs which possess a greater source-identifying power in the eyes of the consumer.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Trade mark protection